Estimating ramping requirements with solar-friendly flexible ramping product in multi-timescale power system operations. (1st September 2018) - Cui, Mingjian; Zhang, Jie
Highlights: A multi-timescale unit commitment and economic dispatch model is developed to estimate the ramping requirements. A solar power ramping product (SPRP) is developed and integrated into the multi-timescale dispatch model. A surrogate-based optimization model is developed to solve the ramping requirements problem. SPRP can reduce the total cost of flexible ramping reserves. Abstract: The increasing solar power penetration causes the need of additional flexibility for power system operations. Market-based flexible ramping services have been proposed in several balance authorities to address this issue. However, the ramping requirements in multi-timescale power system operations are not well defined and still challenging to be accurately estimated. To this end, this paper develops a multi-timescale unit commitment and economic dispatch model to estimate the ramping requirements. Furthermore, a solar power ramping product (SPRP) is developed and integrated into the multi-timescale dispatch model that considers new objective functions, ramping capacity limits, active power limits, and flexible ramping requirements. To find the optimal ramping requirement based on the level of uncertainty in netload, a surrogate-based optimization model is developed to approximate the objective function of the multi-timescale dispatch model that considers both economic and reliability benefits of the balancing authorities. Numerical simulations on a modified IEEE 118-bus system show that a better estimation of ramping requirements could enhance both the reliability and economic benefits of the system. The use of SPRP can reduce the flexible ramping reserves provided by conventional generators.